The weed pollution in Miscanthus giganteus - О. Chernelivska; І. Dziubenko (Карантин і захист рослин)
Goal. Is to determine the species composition of weeds in Miscanthus giganteus plantings, their impact on biomass productivity and the development of an effective protection system.